Do body mass index and waist-to-height ratio over the preceding decade predict retinal microvasculature in 11-12 year olds and midlife adults? - Mengjiao Liu; Kate Lycett; Tien Yin Wong; Jessica A. Kerr; Mingguang He; Markus Juonala; Tim Olds; Terry Dwyer; David Burgner; Melissa Wake (NATURE PUBLISHING GROUP, 2022)
Background/objectives Microvascular changes may contribute to obesity-associated cardiovascular disease. We examined whether body mass index (BMI) and waist-to-height ratio (WHtR) (1) at multiple earlier time points and (2) decade-long trajectories predicted retinal microvascular parameters in mid-childhood/adulthood.
Methods Participants/design: 1288 11-12 year olds (51% girls) and 1264 parents (87% mothers) in the population-based Child Health CheckPoint (CheckPoint) module within the Longitudinal Study of Australian Children (LSAC). LSAC exposure measures: biennial BMI z-score and WHtR for children at five time points from age 2-3 to 10-11 years and self-reported parent BMI at six time points from child age 0-1 years to 10-11 years. CheckPoint outcome measures: retinal arteriolar and venular caliber. Analyses: BMI/WHtR trajectories were identified by group-based trajectory modeling; linear regression models estimated associations between BMI/WHtR at each time point/trajectories and later retinal vascular caliber, adjusted for age, sex, and family socioeconomic status.
Results In time point analyses, higher child BMI/WHtR from age 4 to 5 years was associated with narrower arteriolar caliber at the age of 11-12 years, but not venular caliber. For example, each standard deviation higher in BMI z-score at 4-5 years was associated with narrower arteriolar caliber at 11-12 years (standardized mean difference (SMD): -0.05, 95% confidence interval (CI): -0.10 to 0.01); by 10-11 years, associations had doubled to -0.10 (95% CI: -0.16 to -0.05). In adults, these finding were similar, except the magnitude of BMI and arteriolar associations were similar across all time points (SMD: -0.11 to -0.13). In child and adult BMI trajectory analyses, less favorable trajectories predicted narrower arteriolar (p-trend < 0.05), but not venular (p-trend > 0.1), caliber. Compared with those in the average BMI trajectory, SMDs in arterial caliber for children and adults in the highest trajectory were -0.25 (95% CI: -0.44 to -0.07) and -0.42 (95% CI: -0.73 to -0.10), respectively. Venular caliber showed late associations with child WHtR, but not with BMI in children or adults.
Conclusions Associations of decade-long high BMI trajectories with narrowed retinal arteriolar caliber emerge in children, and are clearly evident by midlife. Adiposity appears to exert its early adverse life course impacts on the microcirculation more via arteriolar than venular mechanisms.